IMPROVING THE CONTENT OF EDUCATION IN PRIMARY SCHOOL - A.B. Ashirbekova (Galaxy International Interdisciplinary Research Journal, 2022)
The article talks about modern education. Examples of improving education through the use of ICT in primary school lessons and their impact on younger schoolchildren are given.